TRANSFORMATION OF MILLENNIAL RELIGIOSITY IN THE DIGITAL ERA: THE ROLE OF SOCIAL MEDIA DA’WAH IN SHAPING INCLUSIVE AND EXCLUSIVE RELIGIOUS ORIENTATIONS - Hanny Rizqiyana Nur'aliya; Hanifatunnisa (El-Ihsan: Journal of Contemporary Islamic Education, 2025)
Da’wah in the digital age has undergone a fundamental shift, with social media becoming the primary channel for disseminating religious messages, particularly among millennials. With 191 million active social media users in Indonesia (We Are Social, 2022), this change has direct implications for the formation of religious attitudes that can be either inclusive or exclusive. This study employs a phenomenological approach to explore the subjective experiences of 10 millennial users of religious outreach platforms such as YouTube, Instagram, and TikTok in consuming and disseminating religious content. Findings indicate that YouTube is chosen for its depth of content, while Instagram and TikTok are preferred for their concise, targeted duration. Positive impacts identified include improved religious literacy and strengthened tolerance values, while the main challenge is the proliferation of provocative content that fuels exclusivism. This study underscores the need for religious digital literacy to maximize the potential of digital da'wah in shaping an inclusive religious identity among millennials.